Transitional pathways towards sustainable food systems - Nhamo, L.; Mpandeli, S.; Liphadzi, S.; Hlophe-Ginindza, S.; Mabhaudhi, Tafadzwanashe (CRC Press, 2024)
Today’s grand challenges, including climate change, resource depletion and degradation, migration, and the emergence of novel pests and diseases, are somehow linked to food systems. The broad interlinkages among these challenges require transformational planning that brings change, enhances adaptation and reduces human and environmental health risks. This chapter applied nexus planning, a transformative approach, to establish the interconnectedness of food systems and developed a framework to guide strategic policy formulations that enhance resource use efficiency, reduce waste in the environment, and ultimately achieve a circular economy. This was achieved through sustainability indicators to provide quantitative transitional pathways that lead to the circular economy in the food value chain. An outline of the available options is given to enhance sustainable food systems, highlighting priority areas for intervention and balancing socio-ecological interactions. The premise was to achieve sustainable food systems by analysing food system components in an integrated manner. Achieving socio-ecological sustainability reduces the risk posed by global environmental change and ensures the continued provision of ecosystem services. Sustainable food systems are a catalyst for achieving socio-ecological balance, and their success hinges on circular modelling and transformative planning.